1998
DOI: 10.1007/s004320050133
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the proliferation index in gastric carcinomas with the monoclonal antibody MIB 1

Abstract: Our study aimed to reveal whether the proliferation index of tumor cells, calculated with the monoclonal antibody (mAb) MIB1, is of prognostic relevance in patients with a gastric carcinoma and shows any correlation to well-known clinicopathological factors (TNM categories, stage, grade, Laurén type). We examined formalin-fixed, paraffin-embedded tissue blocks of samples from 94 patients, who underwent surgery for an adenocarcinoma of the stomach between 1988 and 1991. Specimens were immunohistochemically stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
9
1
Order By: Relevance
“…The MUC‐1 staining pattern in ICP was similar to that in normal pancreatic ductal epithelium, which may indicate that ICP maintains differentiation towards the latter . A high Ki67 labelling index in adenocarcinomas derived from various organs has been reported . The Ki67 labelling index was much higher in ICP samples (5–40%) than in ISMPD (0–3%), indicating increased proliferative activity of ICP.…”
Section: Discussionmentioning
confidence: 54%
“…The MUC‐1 staining pattern in ICP was similar to that in normal pancreatic ductal epithelium, which may indicate that ICP maintains differentiation towards the latter . A high Ki67 labelling index in adenocarcinomas derived from various organs has been reported . The Ki67 labelling index was much higher in ICP samples (5–40%) than in ISMPD (0–3%), indicating increased proliferative activity of ICP.…”
Section: Discussionmentioning
confidence: 54%
“…Immunohistochemical markers including Ki‐67 labeling index have been suggested to have predictive value for LN metastasis in some studies , but it is controversial in other studies . The intratumoral heterogeneity of cell proliferation may be one contributable factor of the reasons for conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…For predicting LN metastasis in EGCs, it has been reported that gastric cancer patients with LN metastases had a significantly higher proliferation index using Ki‐67 immunostaining . However, the Ki‐67 labeling index in gastric cancer has been reported to have no predictable value for LN metastasis or prognostic relevance in other studies . One of contributable factors to this confusion may be heterogeneity of proliferative capacity in tumor area.…”
mentioning
confidence: 99%
“…In a previous publication, the need for a panel of control measurements was emphasized. 4 There are indications in the literature that RT-PCR diagnosis of tumor-associated or tumor-specific antigens in blood or bone marrow can be influenced considerably by certain cytokeratins. Jung and coworkers 28 could detect neither CEA nor cytokeratin 19 (CK19) RT-PCR products either in bone marrow samples from healthy volunteers or in patients with hematologic malignancies, but such products were detected in 60 percent of patients with inflammatory diseases.…”
mentioning
confidence: 99%
“…Results in the literature and from our own clinic show that the prognosis of patients with colorectal cancer is influenced by the occurrence of circulating tumor cells. [1][2][3][4] Prognosis based on ELISA measurements of CEA is highly controversial and may only be feasible by use of serial measurements. One important reason why CEA is established as a tumor marker 5 is that it is an inexpensive and standardized procedure that can be performed automatically.…”
mentioning
confidence: 99%